The Effectiveness Of Total Productive Maintenance (TPM) Implementation In Samsung SDI (M) Berhad - Loong, Lim Kim (2002)
This research study aimed is to discover the factors affecting the successful implementation of TPM. This research has led to the development of a TPM in Samsung SDI(M) indicating factors affecting the successful implementation of TPM.